1993
DOI: 10.1073/pnas.90.17.8000
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human immunodeficiency virus type 1 replication by regulated expression of a polymeric Tat activation response RNA decoy as a strategy for gene therapy in AIDS.

Abstract: We are investigating a strategy for somatic gene therapy to treat human immunodeficiency virus type 1 (HIV-1) infection by intracellular expression of an RNA decoy and a ribozyme. The RNA decoy, consisting of polymeric Tat activation response elements (TARs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0
1

Year Published

1995
1995
2006
2006

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(75 citation statements)
references
References 21 publications
3
71
0
1
Order By: Relevance
“…As well, polymeric TAR sequences may have additive anti-HIV-1 effects when co-expressed with A/tat in CD4 + T cells. 3,22 Antisense RNA against HIV-1, including antisense TAR, has been reported to inhibit HIV-1 when delivered by adeno-associated virus vectors. 23 In the present study, we observed that delivery of TAR 25 + A/tat to cell lines inhibited HIV-1 replication (as determined by HIV-1 p24 antigen levels and syncytium formation) at challenge doses that normally produce large amounts of p24 antigen and extensive cell death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As well, polymeric TAR sequences may have additive anti-HIV-1 effects when co-expressed with A/tat in CD4 + T cells. 3,22 Antisense RNA against HIV-1, including antisense TAR, has been reported to inhibit HIV-1 when delivered by adeno-associated virus vectors. 23 In the present study, we observed that delivery of TAR 25 + A/tat to cell lines inhibited HIV-1 replication (as determined by HIV-1 p24 antigen levels and syncytium formation) at challenge doses that normally produce large amounts of p24 antigen and extensive cell death.…”
Section: Discussionmentioning
confidence: 99%
“…The genes used to test delivery in this system were monomeric and polymeric decoy sequences corresponding to the HIV-1 Tat activation response element (TAR). 3 HIV-1 Tat protein is a trans-activator of transcription for all HIV-1 genes, acting primarily at the level of transcriptional elongation rather than initiation. [4][5][6] Tat function depends on a bulged RNA stem-loop structure, unselected cells in two different human T lymphocyte lines and to unstimulated primary human peripheral blood mononuclear cells (pbmc).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding of RNA Tat to a Tat-2-derived peptide TAR-1 RNA functions as an effector (or decoy) when expressed in HIV-1-infected cultured cells, either as a single or as tandemly connected RNA (Lisziewicz et al 1993). The core regions of Tat-1 and Tat-2 show about 65% homology at the amino acid level.…”
Section: Rna Tat As An Inhibitory Moleculementioning
confidence: 99%
“…34 Ribozymes are potent genetic therapies against HIV, as they cleave both incoming HIV genomic RNA and newly transcribed viral mRNA. 35 HIV-specific ribozymes targeting the 5′ U5 region, 36,37 Tat, 38,39 Rev, Env 40 or Gag 41 have been made and have been shown to inhibit HIV replication. To optimize the inhibiting effects of the protein-based and RNA-based strategies, many studies have used combinations of these diverse molecules: Tat and Rev transdominant mutants, 14,42 transdominant mutant and RNA decoy 43 and RNA decoy and ribozyme.…”
Section: Introductionmentioning
confidence: 99%